Small-scale sea urchin (Tripneustes gratilla) aquaculture: evaluating locally sourced diets for gonad development and quality - Shamira Payet; Maria Rose; Danilla Adonis; Zachary Morin; Aubrey Lesperance; Devis Monthy; Lawrence Grant; Bas De Vos (Western Indian Ocean Journal of Marine Science, 2026)
Sea urchin gonads (called uni) are highly valued in seafood markets, creating demand for sustainable production. In Seychelles, small-scale farming of Tripneustes gratilla is promising, but costly pelleted feeds for gonad enhancement limit feasibility. This study evaluated alternative fresh feeds, Sargassum spp., carrots (Daucus carota), moringa (Moringa oleifera), and a mixed diet, over 10 weeks using 200 T. gratilla (average wet weight: 492.6 ± 79.37 g). Gonad quality was assessed at weeks 6, 8, and 10, alongside disease and mortality monitoring. The overall mean gonadosomatic index (GSI) was 3.34 %, peaking at 10.38 % in week 8. Significant differences were found among feed types and durations (p 0.113), texture (p > 0.071), or firmness (p > 0.064). Mortality and disease rates were also unaffected (p > 0.415 and p > 0.963). Although no tested diet improved gonad quality, the potential for artisanal T. gratilla farming may remain, but likely depends on improved enhancement diets and/or locally feasible formulated feeds, which require further evaluation.

Low mercury content in Seychelles seaweed: implications for aquaculture expansion - Bas De Vos; Shamira Payet; Maria Rose; Clémentine Violette; Rona Arrisol; Margaret Ally-Nourrice; Aubrey Lesperance; Devis Monthy (Western Indian Ocean Journal of Marine Science, 2025)
Stable tropical conditions and a near-pristine marine environment in the Seychelles suggest a high potential for seaweed aquaculture to supply growing global markets for sustainable marine products. The aims of this study were to assess the mercury content in five seaweed species that are candidates for aquaculture in Seychelles: Gracilaria cortica, Gracilaria salicornia, Caulerpa racemosa, Sargassum spp., and Asparagopsis taxiformis. Mercury contamination is a significant con- cern in seaweed aquaculture because it may bioaccumulate, potentially affecting human health when derived products are used. Samples were collected from different sites in Seychelles, categorized as polluted or unpolluted, to evaluate the influence of environmental factors on mercury accumulation. The results showed that mercury contents were low across all tested seaweed species and sites, with the highest observed content of 0.0038 mg/kg (wet weight), well below international safety limits. Significant differences were found between species; however, site pollution level did not significantly influence mercury content. Low mercury content, in addition to a favourable physical environment, confirm that the region is suitable for seaweed aquaculture. It is recommended that other heavy metal concentrations are also assessed, to pro- vide a comprehensive safety evaluation of seaweed aquaculture in Seychelles.

Assessing the potential for red seaweed Asparagopsis taxiformis aquaculture in Seychelles - Bas De Vos; Shamira Payet; Maria Rose; Danila Adonis; Zachary Morin; Devis Monthy; Lawerence Grant; Mookho Lerata; Denzil Beukes; Aubrey Lesperance (Western Indian Ocean Journal of Marine Science, 2025)
Asparagopsis taxiformis macroalgae can potentially reduce methane emissions when fed to ruminants, thus reducing the emission of greenhouse gasses into the atmosphere. Literature indicates water temperatures above 24 °C limit A. taxiformes growth rates during culture, however, it grows wild in Seychelles where water temperatures range from 25 to 31.5 °C. The feasibility of cultivating the local strain of A. taxiformis in Seychelles was investigated, focusing on growth rates at higher temperatures and bromoform content, the compound responsible for methane reduction. Two tetrasporophyte growth trials were conducted in photobioreactors at 24 °C, 26 °C, 29 °C and 32 °C. In the first trial, unacclimated specimens showed poor growth, with no significant differences between temperatures. In the second trial, daily growth rates of acclimated specimens were 3.98 % across all temperatures, including 32 °C, where temperature did not significantly affect growth. Bromoform concentrations were lower than expected, likely due to storage conditions prior to sample processing. The local strain of A. taxiformis in Seychelles may therefore be adapted to higher temperatures, with potential for aquaculture. Further research to optimize cultivation techniques and ensure adequate bromoform content is required.

Sedimentology of Coastal Deposits in the Seychelles Islands—Evidence of the Indian Ocean Tsunami 2004 - Vanessa Nentwig; Heinrich Bahlburg; Devis Monthy (Pure and Applied Geophysics, 2015)